2013
DOI: 10.1016/j.vibspec.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Using Raman spectroscopy to understand the origin of the phase transition observed in the crystalline sulfur based amino acid l-methionine

Abstract: Using Raman spectroscopy to understand the origin of the phase transition observed in the crystalline sulfur based amino acid l-methionine Lima, José A.; Freire, P.T.C.; Melo, F.E.A.; Mendes-Filho, J.; Fischer, Jennifer ; Havenith, Remco W.A.; Broer, R.; Bordallo, Heloisa N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 66 publications
6
14
0
Order By: Relevance
“…The presence of three solid-phase transitions in l -methionine was reported in refs , , and based on measurements performed by the method of thermal analysis. Table shows the data on the temperatures and enthalpies of phase transitions obtained in this work and in refs , , and , which generally indicate the agreement between the results of different works. The exception is the Δ tr H ° value of 7.9 kJ/mol for l -methionine, which is more than double the average value of the remaining references.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The presence of three solid-phase transitions in l -methionine was reported in refs , , and based on measurements performed by the method of thermal analysis. Table shows the data on the temperatures and enthalpies of phase transitions obtained in this work and in refs , , and , which generally indicate the agreement between the results of different works. The exception is the Δ tr H ° value of 7.9 kJ/mol for l -methionine, which is more than double the average value of the remaining references.…”
Section: Resultssupporting
confidence: 81%
“…As seen from Figure , the new data on C p o for l -methionine practically coincide with early measurements in the range 209–320 K, in which a broad peak of the phase transition is observed. Its origin is associated with structural changes in the crystal lattice caused by a decrease in stability and partial deordering due to sequential thermal activation of mobile −S–CH 3 , −CO 2 – , and −NH 3 + groups. , In the region of 320–350 K, the considered data diverge: the decline in the right side of the peak is more pronounced in ref . A likely explanation for this discrepancy is the fact that the C p o in ref is a combination of two sets of measurements performed with different calorimeters in the 11–310 K and 315–350 K intervals.…”
Section: Resultsmentioning
confidence: 99%
“…However, the previous calorimetric studies [ 34 , 36 ], as well as this work, revealed only one phase transition in the temperature region 120– 320 K manifested by a very broad peak with a start around 250 K and a maximum at 307. K. Lima Jr. et al [ 31 ] reported another anomaly in the intensities of some Raman bands in the interval 160–140 K and around 220 K during heat capacity measurements “by relaxation calorimetry (note that the paper does not tabulate any heat capacity data) but not in their DSC experiments. The anomalies scattered over wide temperature ranges are said to be related to conformational changes of at least one of the independent molecules in the unit cell [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…K. Lima Jr. et al [ 31 ] reported another anomaly in the intensities of some Raman bands in the interval 160–140 K and around 220 K during heat capacity measurements “by relaxation calorimetry (note that the paper does not tabulate any heat capacity data) but not in their DSC experiments. The anomalies scattered over wide temperature ranges are said to be related to conformational changes of at least one of the independent molecules in the unit cell [ 31 ]. Based on an unsubstantiated criterion Δ tr S > 1 J mol −1 K −1 , the phase transition with a maximum at 307 K is then established as a first-order transition by authors [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, consideration of results obtained on L-LEU and L-Nle and other hydrophobic amino acids from diffraction, 22,30 thermodynamic 12,35 and vibrational 30,35 investigations suggests that ordering/disordering processes of terminal side-chain groups accompanied with lattice mode softening could be a general phenomenon in this class of materials. This type of phase transition often called displacive phase transition could be considered as a common character of this class of materials which have important and numerous applications in the area of the life sciences.…”
Section: Discussionmentioning
confidence: 99%